Ironic Speech Analysis in the Spontaneous Speech of the Mothers of Lima North Through the Different Pragmatic Theories - Estrada Cubas, Sandra Desiree (2018)
This article reveals the level of irony in certain manifestations that the mothers of Lima North possess in their spontaneous speech. For this, a questionnaire was made with eleven questions, which contain common information in communication between mothers and offspring; these are grouped according to common features and the most plausible pragmatic theories are applied to the analysis of the data. Likewise, a generalization of the data obtained is sought, based on the theories applied. It is concluded that the levels of irony practiced (consciously and unconsciously) by mothers are changing and will depend on the type of question they have been asked, because in some cases they do not use this resource. Also, rhetorical phrases and figures that accompany the figurative sense of ironic statements are considered.